Field notes contributed by Raymond L. Cummins, fall 1988 - Cummins, Raymond L.et al (1988)
List of birds and locations contributed by Raymond L. Cummins with observers Dot Cornett. This item was used as supporting documentation for the Iowa Ornithologists Union Quarterly field report of fall 1988. Epson - sheet feed